Can youth at high risk of illness progression be identified by measures of rumination and sleep‐wake disturbance. Issue 5 (28th November 2018) - Grierson, Ashlee B.; Scott, Jan; Glozier, Nick; Hickie, Ian B.; Amminger, Paul G.; Killackey, Eoin; McGorry, Patrick D.; Pantelis, Christos; Phillips, Lisa; Scott, Elizabeth; Yung, Alison R.; Purcell, Rosemary
Abstract : Aim: Clinical staging models offer a useful framework for understanding illness trajectories, where individuals are located on a continuum of illness progression from stage 0 (at‐risk but asymptomatic) to stage 4 (end‐stage disease). Importantly, clinical staging allows investigation of risk factors for illness progression with the potential to target trans‐diagnostic mechanisms at an early stage, especially in help‐seeking youth who often present with sub‐threshold syndromes. While depressive symptoms, rumination and sleep‐wake disturbances may worsen syndrome outcomes, the role of these related phenomena has yet to be examined as risk factors for trans‐diagnostic illness progression in at‐risk youth. Methods: This study is a prospective follow‐up of 248 individuals aged 12 to 25 years presenting to headspace services with sub‐threshold syndromes (stage 1) classified under the clinical staging model to determine transition to threshold syndromes (stage 2). Factor analysis of depression, rumination and sleep‐wake patterns was used to identify key dimensions and any associations between factors and transition to stage 2 at follow‐up. Results: At 1 year, 9% of cases met criteria for stage 2 (n = 22). One of three identified factors, namely the factor reflecting the commonalities shared between rumination and sleep‐wake disturbance, significantly differentiated cases that transitioned to stage 2 vs those that did not demonstrate transition. Items loading onto this factor, labelled Anergia, included depression severity and aspects of rumination and sleep‐wake disturbance that were characterized as introceptive. Conclusions: Common dimensions between rumination and sleep‐wake disturbance present a detectable trans‐diagnostic marker of illness progression in youth, and may represent a target for early intervention.